Pain, experience, and well-being - Kahane, G (Routledge, 2015)
We have all felt pain. We enter this world screaming, and we hope to leave it painlessly. In between, our lives are punctuated by moments of pain, often brief and negligible, a mere distraction, but at other times mind-blowingly intense and debilitating, stretching for hours, days, even months and years. Then there are unpleasant experiences such as nausea, an upset stomach, a numb foot or itching scalp, and other kinds of bodily discomfort. Not to mention heartache, bitter disappointment, loss, despair, depression, hopelessness . . .